Customer Experience, Brand Image and Its Impact Towards Revisit Intention to Batavia Café Jakarta - Maulina, Anita; Sofyan Fauzi, Mohammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The diversity of people who live in big cities like Jakarta makes consumer demand and tastes always change. This makes the culinary business more enthusiastic to meet market demand and compete with other culinary business owners. In an effort to maintain market share and competitiveness, culinary and restaurant business actors can focus on the experience gained by customers during consumption rather than just selling products or services. Loyal visitors are very impactful for restaurant business managers. They will come back again to visit, write positive reviews on social media or blogs and even recommend to relatives, friends, friends to visit a certain restaurant that is considered good and interesting and worth visiting. Therefore, business owners or restaurant managers must be able to build a positive image of the restaurant. One of the efforts to build a positive image is through the brand.One of them is Café Batavia which has a building dating from the Dutch colonial period. Previously this building was the official residence of the Dutch Governor. The building is a cultural heritage that is very well preserved. The interior design is intentionally made in accordance with the Dutch colonial period so that visitors feel they are in the past. This uniqueness is not easily obtained in other places so that this can be a differentiator for culinary lovers and make Café Batavia have its own brand image in the minds of its consumers. However, local tourists' interest in visiting Cafe Batavia (20%) is only slightly due to the price of food which tends to be expensive and mostly western and chinese food. Cafe Batavia serves many menus such as wine, cocktails, or other menus that are difficult to accept or may only be enjoyed by certain circles of the local community. This study uses a quantitative approach, has an unknown population of customers of Café Batavia Jakarta. The sample size was obtained by 5x24 indicators, namely 120 consumers with a sampling technique, namely purposive sampling. The final conclusion is that customer experience and brand image have a positive and significant effect on revisit intention. It is also recommended several things related to repeated visits for future research purposes.